Stabilization of Sandy Soil Against Internal Erosion Using Fly Ash Mixed with Alkali-Activated Binder - Almasaeid, Mohammad Suleiman (2022)
A Master of Science thesis in Civil Engineering by Mohammad Suliman Almasaeid entitled, “Stabilization of Sandy Soil Against Internal Erosion Using Fly Ash Mixed with Alkali-Activated Binder”, submitted in November 2022. Thesis advisor is Dr. Mousa Attom. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).